2018
DOI: 10.1016/j.freeradbiomed.2018.05.060
|View full text |Cite
|
Sign up to set email alerts
|

Sulfiredoxin-1 enhances cardiac progenitor cell survival against oxidative stress via the upregulation of the ERK/NRF2 signal pathway

Abstract: Cardiac stem/progenitor cells (CPCs) have recently emerged as a potentially transformative regenerative medicine to repair the infarcted heart. However, the limited survival of donor cells is one of the major challenges for CPC therapy. Our recent research effort on preconditioning human CPCs (hCPCs) with cobalt protoporphyrin (CoPP) indicated that sulfiredoxin-1 (SRXN1) is upregulated upon preconditioning aldehyde dehydrogenase bright hCPCs (ALDH-hCPCs) with CoPP. Further studies demonstrated that overexpress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 56 publications
0
27
0
Order By: Relevance
“…MAPK signaling is known to be connected with Srx-1 expression. For example, Srx-1 was shown to enhance the survival of cardiac cells against oxidative stress through increased expression of the ERK signaling [ 35 ]. When mouse skin epithelial JB6 cells were combined treated with TPA and chemical inhibitors such as the ERK inhibitor PD98059 or the JNK inhibitor SP600125, TPA-induced Srx-1 expression was decreased [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…MAPK signaling is known to be connected with Srx-1 expression. For example, Srx-1 was shown to enhance the survival of cardiac cells against oxidative stress through increased expression of the ERK signaling [ 35 ]. When mouse skin epithelial JB6 cells were combined treated with TPA and chemical inhibitors such as the ERK inhibitor PD98059 or the JNK inhibitor SP600125, TPA-induced Srx-1 expression was decreased [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…SRX1 was identified as a pivotal NRF2-regulated gene responsible for the defense against oxidative injury in the lung induced by cigarette smoke (15). Another study demonstrated that SRX1 protected human cardiac stem/progenitor cells against oxidative stress-induced apoptosis through the activation of the ERK/NRF2 signaling pathway (18). NRF2 has also been reported to activate the antioxidant response element-dependent gene expression of HO-1, NQO1 and SOD through evading Kelch-like ECH-associated protein 1 (KEAP1)-mediated ubiquitination-proteasomal degradation and subsequent nuclear translocation (42).…”
Section: Discussionmentioning
confidence: 99%
“…SRX1 was also identified to have a crucial role in cellular damage triggered by oxidative stress (16,17). Moreover, SRX1 protected cardiac progenitor cells from oxidative stress and promoted their survival via ERK/NRF2 signaling (18). Another study also illustrated the cardioprotective effect of SRX1 via the inhibition of mitochondrial apoptosis through the PI3K/AKT signaling pathway (19).…”
Section: Inflammatory Response and Oxidative Stress Attenuated By Sulmentioning
confidence: 97%
“…So far, more than 200 target genes of NRF2 have been described in humans [59]. The vast majority of them encode for metabolic enzymes that readily detoxify electrophiles (i.e., phase I/II/III drug metabolism) or scavenge ROS molecules (i.e., antioxidant systems) [60, 61], in order to restore the intracellular redox homeostasis and minimize the oxidative damage [60, 62]. However, increasing evidence indicates that NRF2 can also regulate other biological processes with physiopathological relevance in human diseases (e.g., tumors) such as proliferation [6267], differentiation [6872], inflammation [7376], autophagy [7781], apoptosis [66, 8285], mitochondrial function or biogenesis [8692], and several metabolic pathways involved in iron/heme [32, 9397], glucose [98101], glutamine [101103], lipid [104107], NADPH [108–110], and pentose phosphate metabolism [111114].…”
Section: Nrf2/keap1 Pathway: a Master Regulator Of Stress Responsesmentioning
confidence: 99%